Geomorphologic micro basin Pastoruri-Cordillera Blanca - Durand Castro, David (2009)
The following geomorphologic study about thy micro-basin of the «Pastoruri» glacier, covers the most important characteristics on the configuration of relief, as essential aspects of the morfo-dynamic and morpho-genetic processes that work in its glacial and periglacial model. This research develops investigation assignments in order to accomplish with the goal of moving forward in the knowledge of the glacial processes that effects our planet, its relationship with the weather changing and its effects in the availability of hydro resources. It deals with a